THE ETHNOPSYCHOLOGICAL APPROACH TO STUDYING THE CHARACTERISTICS OF RELATIONSHIPS BETWEEN PARENTS AND THE ELDEST CHILD - K. Kasimova (Bright Mind Publishing, 2025)
The article examines the ethnocultural characteristics of parent-child relationships, focusing on the interactions between parents and their eldest child. It explores the influence of cultural traditions, values, and societal norms on parental expectations, upbringing practices, and the child's role within the family structure. The study highlights cross-cultural differences in family dynamics and emphasizes the impact of historical and social contexts on parenting styles. The findings contribute to a deeper understanding of how ethnocultural factors shape the psychological and emotional development of the eldest child.
Keywords: Ethnocultural characteristics, parent-child relationships, eldest child, upbringing practices, family dynamics, cultural traditions, parenting styles, social norms.